Mathematical Modeling and Stability Analysis of Systemic Risk in the Banking Ecosystem - Irène Irakoze; Fulgence Nahayo; Dennis Ikpe; Samuel Asante Gyamerah; Frederi Viens (Journal of Applied Mathematics)
This paper investigates the dynamics of systemic risk in banking networks by analyzing equilibrium points and stability conditions. The focus is on a model that incorporates interactions among distressed and undistressed banks. The equilibrium points are determined by solving a reduced system of equations, considering both homogeneous and heterogeneous scenarios. Local and global stability analyses reveal conditions under which equilibrium points are stable or unstable. Numerical simulations further illustrate the dynamics of systemic risk, while the theoretical findings offer insights into the behavior of distressed banks under varying conditions. Overall, the model enhances our understanding of systemic financial risk and offers valuable insights for risk management and policymaking in the banking sector.